Phytochemical investigations on the leaves of the plant Clerodendrum viscosum Vent. - Md. Ataur Rahman; Nusrat Jahan; Md. Jahirul Islam (Journal of Science, 2026)
One steroidal compound (22E, 24S)-stigmasta-5, 22, 25-trien-3β-ol and a non-steroidal compound, clerodin have been isolated from the n-hexane extract of the leaves of the plant Clerodendrum viscosum Vent. The isolated compounds were characterized on the basis of their physical properties and spectroscopic data analysis.